TECHNOLOGICAL ASPECTS OF PRESERVATION PROCESSIG Of EDIBlE SHELL FISHES II.INFLUENCE Of SEASON ON THE CHEMICAL COMPOSITION OF CRAB (SCYLLA SERRATA) - GEORGE, CHINNAMMA; JAMES, M ARUL (Fishery Technology, 2025)
The purpose of this communication is to bring out the influence of season on the chemical composition of crab, covering a period of 2 years. Changes in moisture, protein, water extractable nitrogen, non-protein nitrogen, glycogen, lactic acid, fat and free amino acid composition of crab meat have been reported on a monthly basis